2008
DOI: 10.1016/j.nuclphysb.2007.07.013
|View full text |Cite
|
Sign up to set email alerts
|

The soft-energy region in the radiative decay of bound states

Abstract: The orthopositronium decay to three photons is studied in the phase-space region where one of the photons has an energy comparable to the relative three-momentum of the e+e- system (w ~ m alpha). The NRQED computation in this regime shows that the dominant contribution arises from distances ~ 1/(mw)^(1/2), which allows to treat the Coulomb interaction perturbatively. The small-photon energy expansion of the 1-loop decay spectrum from full QED yields the same result as the effective theory. By doing the thresho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 33 publications
3
8
0
Order By: Relevance
“…In three-body channels, the energy of decay products has an extended distribution. Its low-energy tail is sensitive to binding effects; such effects have been determined in the three-photon decay of o-Ps [23][24][25][26]. We find analogous phenomena in the Ps → γν ν decay.…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…In three-body channels, the energy of decay products has an extended distribution. Its low-energy tail is sensitive to binding effects; such effects have been determined in the three-photon decay of o-Ps [23][24][25][26]. We find analogous phenomena in the Ps → γν ν decay.…”
Section: Introductionsupporting
confidence: 59%
“…While normally the dipole approximation is applicable for photons with wavelengths much larger than the spatial extent of the Ps atom, 2/mα (i.e., E γ mα), it has been shown that the dipole approximation of the Coulomb interaction Hamiltonian holds in the enlarged energy region E γ m for the three-body decay o-Ps → 3γ [25,26]. In this energy region, amplitudes where the intermediate states propagate via the Coulomb Green's function, are a series in α m/E γ ∼ √ α rather than integer powers of α.…”
Section: B Dipole Approximation Of the Coulomb Interaction Hamiltonianmentioning
confidence: 99%
See 1 more Smart Citation
“…The Non-Relativistic QED (NRQED) framework used in Refs. [1,2] provides a systematic way to compute bound state effects in the the o-Ps decay spectrum when the photon energy is much smaller than the electron mass. Contrary to the usual relativistic approach where the 3photon annihilation is considered to take place at very short distances as compared to the range of the electromagnetic binding force between e + e − , the non-relativistic description takes into account that there is a long-distance part in the o-Ps decay process when one the photons in the final state is not hard (ω m).…”
Section: Nrqed Computation Of the O-ps Decay Spectrum For ω Mmentioning
confidence: 99%
“…1). The emission of the low energy photon from o-Ps is described by the Coulomb Hamiltonian of the e + e − system in interaction with a quantized electromagnetic field [1,2].…”
Section: Nrqed Computation Of the O-ps Decay Spectrum For ω Mmentioning
confidence: 99%